ANALYSIS OF THE IMPACT OF THE HIGH SCHOOL DOUBLE TRACK PROGRAMME ON STUDENT SKILL AND CHARACTER DEVELOPMENT - Haniatur Rofiqoh Umar; Yosi Mariana; Sudarmiatin; Mokhammad Nurruddin Zanky (CV Naskah Aceh, 2026)
The Double Track High School Program, created by the East Java Provincial Government aims to simultaneously provide students with character and vocational competencies. However, previous research findings on the impact of this program are still fragmented, making it difficult to gain a comprehensive understanding of its